2017
DOI: 10.1073/pnas.1704117114
|View full text |Cite
|
Sign up to set email alerts
|

Structural variants caused byAluinsertions are associated with risks for many human diseases

Abstract: Interspersed repeat sequences comprise much of our DNA, although their functional effects are poorly understood. The most commonly occurring repeat is the Alu short interspersed element. New Alu insertions occur in human populations, and have been responsible for several instances of genetic disease. In this study, we sought to determine if there are instances of polymorphic Alu insertion variants that function in a common variant, common disease paradigm. We cataloged 809 polymorphic Alu elements mapping to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 84 publications
7
111
0
Order By: Relevance
“…Indeed, it is known that the RNA helicase Upf1 can sense 3'-UTR size and 490 promote nonsense mediated decay of abnormally long 3'-UTRs [62]. Also, because we 491 cloned the "presence" and "absence" 3'-UTR haplotypes from two different LCLs, we 492 cannot rule out that another polymorphism 'hitchhiking' with the Alu insertion, is causing 493 as well as the many other TE-QTLs identified in this study underscore a plausible 501 contribution of TE insertions commonly segregating in the population in human trait 502 variation, including disease susceptibility [16,19,63]. These findings confirm the 503 potential of unfixed TEs to make a non-trivial contribution to human gene expression [5-504 7].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, it is known that the RNA helicase Upf1 can sense 3'-UTR size and 490 promote nonsense mediated decay of abnormally long 3'-UTRs [62]. Also, because we 491 cloned the "presence" and "absence" 3'-UTR haplotypes from two different LCLs, we 492 cannot rule out that another polymorphism 'hitchhiking' with the Alu insertion, is causing 493 as well as the many other TE-QTLs identified in this study underscore a plausible 501 contribution of TE insertions commonly segregating in the population in human trait 502 variation, including disease susceptibility [16,19,63]. These findings confirm the 503 potential of unfixed TEs to make a non-trivial contribution to human gene expression [5-504 7].…”
mentioning
confidence: 93%
“…To date, whole genome sequencing studies have discovered 42 more than 19,000 TE loci segregating in the human population [11][12][13][14][15]. Despite their 43 potential role in shaping human phenotypic variation, including disease 44 susceptibility [16,17], very little is known about the impact of these polymorphic 45 insertions on genome function. Only a handful of recent studies have started to unravel 46 their contribution to gene expression variation [16][17][18][19].…”
mentioning
confidence: 99%
“…Nevertheless, more than 70 de novo Alu insertions are known to cause genetic diseases (Hancks and Kazazian 2016), including neurological disorders (Larsen et al 2018; Hueso et al, n.d.). Furthermore, polymorphic Alu insertions have been identified as candidate causative variants in common polygenic diseases (Payer et al 2017), and a handful have been shown to alter mRNA splicing (Payer et al 2019). Finally, worldwide reference pMEI datasets such as those produced by 1000 GP (Sudmant et al 2015) can be used in conjunction with gene expression data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Primate specific Alu retrotransposons, which occupy ~11% of the human genome, are major players in this process (1,7). These provide non-canonical transcription factor binding sites and other regulatory sites that govern epigenetic modifications as well as provide cryptic splice sites that lead to alternative splicing or differential mRNA stability (5,(8)(9)(10)(11)(12)(13)(14). Alu-derived exons exhibit lineage specificity with high transcript inclusion levels and have much higher rates of evolution (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%